Ambient air pollution and allergic diseases in children - Byoung-Ju Kim; Soo-Jong Hong (Korean Pediatric Society, 2012)
The prevalence of allergic diseases has increased worldwide, a phenomenon that can be largely attributed to environmental effects. Among environmental factors, air pollution due to traffic is thought to be a major threat to childhood health. Residing near busy roadways is associated with increased asthma hospitalization, decreased lung function, and increased prevalence and severity of wheezing and allergic rhinitis. Recently, prospective cohort studies using more accurate measurements of individual exposure to air pollution have been conducted and have provided definitive evidence of the impact of air pollution on allergic diseases. Particulate matter and ground-level ozone are the most frequent air pollutants that cause harmful effects, and the mechanisms underlying these effects may be related to oxidative stress. The reactive oxidative species produced in response to air pollutants can overwhelm the redox system and damage the cell wall, lipids, proteins, and DNA, leading to airway inflammation and hyper-reactivity. Pollutants may also cause harmful effects via epigenetic mechanisms, which control the expression of genes without changing the DNA sequence itself. These mechanisms are likely to be a target for the prevention of allergies. Further studies are necessary to identify children at risk and understand how these mechanisms regulate gene-environment interactions. This review provides an update of the current understanding on the impact of air pollution on allergic diseases in children and facilitates the integration of issues regarding air pollution and allergies into pediatric practices, with the goal of improving pediatric health.